(untitled) (Bangladesh Pharmaceutical Journal, 2024)
Hair loss in adult men albeit common, can cause emotional distress. Many people with hair fall issues try chemical-based treatments that may lead to health complications and allergic reactions. Cosmetics using natural ingredients derived from plants have fewer side effects compared to synthetic alternatives. The study aimed to formulate herbal hair oil using various ingredients like castor oil, sunflower oil, jojoba oil, olive oil, pumpkin oil, etc. and evaluate its effectiveness in promoting hair growth and prevention of hair fall (HG-HF). Besides, the oil was supposed to provide a range of benefits for hair health, including preventing dandruff, improving scalp health, providing antioxidant properties, and thereby protecting against oxidative damage. The DPPH radical scavenging test was done to evaluate the antioxidant activity of the oils. Varying IC50 values were found such as olive oil and sunflower oil showed IC50 values of 3.79 μg/ml and 4.44 μg/ml respectively. Hence, these oils have significant antioxidant activity with a strong ability to scavenge or neutralize free radicals. A study was conducted on sixteen volunteers with hair loss, dandruff, and other hair problems to check the performance of the oil. 56.25% of the participants experienced increased hair growth and 50% reported a decrease in hair fall after using the oil for 3 months, with no remarkable side effects. Data demonstrated effectiveness and overall acceptable perception of the HG-HF oil by the participants. Bangladesh Pharmaceutical Journal 27(1): 9-18, 2024 (January)